The pharmaceutical care and the rejected constitutional reform: what might have been and what is - Siracusa, Margherita; Grappasonni, Iolanda; Petrelli, Fabio (Acta Biomedica Atenei Parmensis, 2017)
This study analyzes the current state of legislation pertaining to pharmaceutical/health care in a period of normative ferment characterized by continuous changes, after countless discussions that have been held on a proposed constitutional reform (rejected by the will of the people at the end of 2016). After a general reflection on the division of legislative powers between the State and its Regions, in the light of attempts to bring about a reform, we will analyse specific problems: from the recent, but in some ways already defined as historic, approval of the new Essential Levels of Care (LEC), the approval of the 2017 Budget Law (concerning important items such as the purchase of drugs), until we reach the Draft Law on competition which is in the process of being approved. All this is taking place in the context of loyal, unavoidable cooperation between State, Regions and local institutions, in the spirit of the ascendancy of the right to health over economic/financial interests in the country.